Emulating a Target Trial of Early Compared to Late Initiation of Appropriate Antibiotic Therapy for Hospital-acquired Monobacterial Gram-negative Blood Stream Infections - Abdullah Tarik Aslan; Yukiko Ezure; Elif Seren Tanriverdi; Osman Dag; Cansu Cimen; Baris Otlu; Patrick Harris; Murat Akova; David L. Paterson (Journal of Global Antimicrobial Resistance)
Background: Considering the difficulties and ethical concerns to conduct a randomized controlled trial comparing early appropriate antimicrobial treatment (<24h) versus late initiation of appropriate therapy (24-72h) in Gram-negative bacterial (GNB) infections, we conducted a target trial emulation framework to appreciate the casual effect of early appropriate antimicrobial treatment (EAT) compared to late initiation of appropriate therapy (LAT) on clinical outcomes in patients with hospital-acquired monobacterial Gram-negative blood stream infection (BSI). Method: The emulated trial included individuals recruited in a prospective cohort of adult patients from 22 Turkish hospitals between September 2021-December 2022. Data pertaining to eligibility criteria, treatment strategies, treatment assignments, follow-up, outcomes, and statistical analysis are shown in Table 1. RESULTS: 378 individuals were included (mean age, 59.5 ± 17.7 years; 65 % males). Most frequent sources of infection included pneumonia (21.2%) and central venous catheters (13.8%). 54.2% were treated in ICU at the onset of the BSI with a mean SOFA score of 6.1 ± 4.2. Difficult-to-treat resistance was present in 24.6% of the causative pathogens. The 28-day mortality rate was 26.1% in the EAT group vs 40.6% in 24-72h group. Table 2 shows the results of inverse probability treatment weighting-adjusted analysis of main analysis population and those of subgroup analyses comparing clinical outcomes in very EAT (<6h) vs those initiated beyond 6 hours of the onset of BSI. CONCLUSIONS: Both EAT and very EAT compared to LAT reduced the risk of mortality but had no significant effect on clinical cure in BSIs caused by monobacterial GNB.